2008
DOI: 10.1093/jn/138.2.332
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Soy Protein Isolate Ameliorates Atherosclerotic Lesions in Apolipoprotein E-Deficient Mice Potentially by Inhibiting Monocyte Chemoattractant Protein-1 Expression1, ,3

Abstract: Soy-based diets reportedly protect against the development of atherosclerosis; however, the underlying mechanism(s) for this protection remains unknown. In this report, the mechanism(s) contributing to the atheroprotective effects of a soy-based diet was addressed using the apolipoprotein E knockout (apoE-/-) mice fed soy protein isolate (SPI) associated with or without phytochemicals (SPI+ and SPI-, respectively) or casein (CAS). Reduced atherosclerotic lesions were observed in aortic sinus and enface analyse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
50
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 59 publications
(52 citation statements)
references
References 27 publications
1
50
0
Order By: Relevance
“…MCP-1, a member of the CC chemokines, is involved in both recruitment of monocytes and lipid deposition into arterial walls, thereby enhancing the progression of atherosclerosis [19]. Previous studies have reported that both absence of MCP-1 and inhibition of adhesion molecule expression ameliorate atherosclerosis in various atherosclerotic models including low-density lipoprotein receptor-deficient mice [18], apoE–/– [20] mice, and high-cholesterol-fed rabbits [21,22]. Therefore, downregulation of proatherogenic genes may have ameliorated the development of atherosclerotic lesions in this study.…”
Section: Discussionmentioning
confidence: 99%
“…MCP-1, a member of the CC chemokines, is involved in both recruitment of monocytes and lipid deposition into arterial walls, thereby enhancing the progression of atherosclerosis [19]. Previous studies have reported that both absence of MCP-1 and inhibition of adhesion molecule expression ameliorate atherosclerosis in various atherosclerotic models including low-density lipoprotein receptor-deficient mice [18], apoE–/– [20] mice, and high-cholesterol-fed rabbits [21,22]. Therefore, downregulation of proatherogenic genes may have ameliorated the development of atherosclerotic lesions in this study.…”
Section: Discussionmentioning
confidence: 99%
“…However, studies have shown that atherosclerotic lesions are reduced in atherosclerosis-susceptible apolipoprotein E knockout (apoE-/-) mice fed a soy-containing diet despite unchanged serum lipid levels (Adams et al, 2002;Nagarajan et al, 2008). Moreover, intervention studies in humans have shown that the favorable effects of soy protein on vascular function are independent of lipid and antioxidant effects (Steinberg et al, 2003).…”
Section: Table 1 the Principal Aspects Of A Mediterranean Dietmentioning
confidence: 99%
“…Moreover, intervention studies in humans have shown that the favorable effects of soy protein on vascular function are independent of lipid and antioxidant effects (Steinberg et al, 2003). Soy protein has anti-inflammatory properties, and the mechanisms of soymediated inhibition of atherosclerosis are considered to be anti-inflammatory (Nagarajan et al, 2008). The importance of isoflavones has been disputed because the favorable effects of soy can be elicited by soy protein devoid of isoflavones (Balmir et al, 1996;Nagarajan et al, 2008;Song et al, 2003).…”
Section: Table 1 the Principal Aspects Of A Mediterranean Dietmentioning
confidence: 99%
See 1 more Smart Citation
“…Apolipoprotein E (ApoE)-deficient mice develop severe hypercholesterolemia and atherosclerotic lesions in a manner similar to humans (23,24), and they are used extensively as a model for atherosclerosis research (25). In these mice, cigarette smoking has been reported to accelerate atherogenesis (26,27).…”
Section: Introductionmentioning
confidence: 99%